Answer:
Explanation:
Problem One
- sqrt(2x + 10) - 6 = 2 Add 6 to both sides
- sqrt(2x + 10) = 2 + 6
- sqrt(2x + 10) = 8 Square both sides.
- sqrt(2x + 10)^2 = 8^2 Do the operation
- 2x + 10 = 64 Subtract 10 from both sides
- 2x + 10 - 10 = 64 - 10 Combine
- 2x = 54 Divide by 2
- 2x/2 = 54/2
- x = 27
Problem Two
Problem two has a small problem. The way it is written suggests that the question number might be seven. Maybe that's why you get a second answer.
f(x) = - 2x + 4
g(x) = -6 - 7 I'm assuming the 7 is a counting number and not the question number
g(x) = - 13
f(x) - g(x) = -2x + 4 - - 13
f(x) - g(x) = -2x + 4 + 13
f(x) - g(x) = - 2x + 17
Now suppose it is the question number
f(x) - g(x) = - 2X + 4 - 6
f(x) - g(x) = - 2x - 2